Pengembangan reading box untuk meningkatkan minat baca mahasiswa - Andreani, Sri; Astuti, Utari Praba (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
Due to the unavailability of materials for the Reading II subject, this study attempts to develop a reading box material which consists of 80 units of 400–500 words. Each unit contains an introduction, questions, readings, answer keys, reflections, and monitoring books. This reading box enables students to practice reading extensively and independently. This material was developed through several stages: planning, exploration, product development, validation, and laminating. During validation, revisions were made to the questions, readings, answer keys, reflections, illustrations, layout, the title, and the monitoring book. However, the results of the questionnaire on the validation process show that the material was qualified in terms of content, the appropriateness of the reading types and topics to students’ interests and intelligence, the length of the readings, the variety of text types, the difficulty level, illustrations, layout, font, and letter size.